Hybridization in Kaplan turbines. Wear and tear assessment. Issue 1 (1st September 2022) - Valentín, David; Presas, Alexandre; Egusquiza, Mònica; Valero, Carme
Abstract: In the current energy market, hydraulic turbines are increasingly demanded to work in Frequency containment reserve (FCR) mode to compensate the constant frequency fluctuations in the electrical grid. To do so, hydraulic turbines change their generating power continuously which implies to regulate the flow rate. Kaplan turbines are double regulated machines that change the position of both guide vanes and runner blades to regulate the flow rate maximizing their efficiency. Therefore, guide vanes and runner blades are continuously moving when they provide FCR, leading to high wear and tear of the regulation system components. Within the frame of the European project XFLEX Hydro, a new technology to reduce the wear and tear of the regulation system in FRC have been implemented. This technology consists in the hybridization of the unit with a battery system. In that way, the battery is the one in charge of providing part of the power fluctuations to the grid, reducing the movements of guide vanes and runner blades of the turbine. The battery system was successfully installed in August 2021 in one unit of the Vogelgrun powerplant, in France. Since that moment, the unit has been working in hybrid mode. A monitoring system was installed in the power plant in two different units, the one hybridized and another without hybrid system. Several sensors were installed and different parameters were measured simultaneously to calculate the wear and tear of the different components. In this paper, a comparison between the hybrid mode and the standard mode (non-hybrid) is performed in terms of mileage and wear and tear of the guide vanes and runner blades servomotors.